Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2019)
A dataset containing 2172391 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 2172391 records from 21781 constituent datasets: 208 records from Condamine Alliance. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 181 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 139 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 9 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 5516 records from Comparative study in validity of three regions of 18S-rRNA for eukaryote amplicon sequence analyses. 1156 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 367 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 15 records from Tardigrad collection of the National Museum of Nature and Science. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 4 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 1701 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 170 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 107 records from Faunal assemblage of sediment core TR149-31. 1626 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 17364 records from Microbial community in marine sediments. 599 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 18 records from Naturtag. 8 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 16071 records from Herbier Louis-Marie (QFA) - Collection de lichens. 59 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 164952 records from Oiseaux nicheurs de France métropolitaine 2009-2012 - Nidification probable. 93 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 204 records from Planktic foraminifera abundance of Hole 29-284A. 73 records from Planktic foraminifera abundance of Hole 49-409. 4 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 3 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 2 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 1551 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 774 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO. 120 records from Total foraminifera counts of multinet M21/2_MSN650. 7283 records from Colecção Entomológica IIA. 6702 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 16763 records from MZFC/Coleccion de Aves. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 52 records from Nannofossil abundance of Hole 10-91. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR64. 1017 records from DMNS Egg Collection (Arctos). 2538 records from (Table 2) Nannofossil occurrence in ODP Hole 101-627B. 13203 records from Lepidopterous specimens of Yamagata Prefectural Museum. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 262 records from Chronicle of Nature - Phenology of Mushrooms of Pechoro-Ilych State Nature Reserve. 7 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 5462 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 238 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 9 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 287870 records from Florida Keys Reef Visual Census 2014. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 28 records from Phytoplankton abundance at station Casma_2003-01-30_2, Casma, Peru. 361 records from An updated checklist of aquatic plants of Myanmar and Thailand. 1702 records from BioGIS - Bryophytes - HUJ collections. 2 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 1 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 45970 records from Herbarium Universitatis Daugavpiliensis. 592 records from Colección de Entomología - Curculionidae. 158 records from Planktic foraminifera counts at CTD station M39/4_402CTD-55. 2208 records from marine sediment metagenome Raw sequence reads. 13 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 393 records from Dinoflagellate cyst counts on sediment core ABC26. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 306 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 1 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 22156 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 971 records from azorean_vascular plants. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 423 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 6230 records from Plecoptera. 5 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 23660 records from Swan Coastal Plain Survey. 9 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 80 records from Total foraminifera counts of multinet M21/4_MSN704. 184 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 14 records from NZCS Brownsberg Nature Park Monitoring. 143 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 62116 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 66 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 35 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 20 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 383 records from Neogene palynomorpha from site 81-552. 120 records from BIRDRACE The early birds. 1289 records from RECORD Orthoptera Data. 92 records from Protozoa Abundance_Microbial Parameters. 17 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 55 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 59788 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 32 records from Antarctic Pycnogonids II. 10 records from Oberservation of birds at station PS14/143 along 49° West. 1763 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 2560 records from Upper Silesian Museum, Bird Observations. 69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 1628 records from Données naturalistes de Quentin ROME. 798 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 223 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 126 records from SEWBReC Springtails and allies (South East Wales). 1 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 2076 records from Planktic foraminifera assemblage in sediment core SO42-74KL. 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 49 records from Nannofossil abundance of Hole 9-79. 108 records from Benthic foraminifera abundance in ODP Leg 155 holes. 101808 records from The Himalayan Uplands Plant database (HUP Version 1). 131 records from Artenvielfalt auf dem Schulgelände. 7840 records from National Museum of Natural Science. 165 records from Diversidad de anfibios en tres coberturas vegetales y su relación con actividades antrópicas (amenazas) presentes en el Parque Nacional Natural Tatamá y su área de influencia.. 11 records from (Table 2) Population density and zoobenthos biomass in bottom communities of the Novosibirsk Polynya in September 2008. 238 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 69 records from Global Ocean Sampling Expedition. 69 records from BIRDRACE Pfeifenten. 11 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 42 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 6158 records from Marine metagenome ICM_JRV. 52 records from Collections ichtyologiques et herpétologiques (BOUM). 288 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 8516 records from Données naturalistes de Bruno OGER. 1 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 6192 records from NE Scotland fish records 1800-2010. 301 records from Marine sediment metagenome ICM_GMS. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 609 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 648 records from Range table from planktonic foraminifers in ODP Hole 155-930B. 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 1014 records from Pollen profile ADR353. 97 records from Foraminifera species abundances from tow TT011_7-MOC66. 6 records from Sächsische Schweiz (Pfaffenstein). 11944 records from Données ONEMA BDMAP 2014. 564 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 1026 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 115 records from Living Cirripedia. 7 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 510 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 1087 records from Tree species composition of natural forest islands in a savanna matrix in the northern Brazilian Amazonia. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 84 records from Roter Berg Werdau (Leubnitz). 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 3755 records from Données naturalistes de Charlotte PICARD. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 5 records from Ostracoda abundance of Hole 44-390. 2 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 131 records from Manejo campesino sustentable del maguey papalote del Chilapan. Fase II. 24095 records from University of California Santa Barbara Invertebrate Zoology Collection. 285 records from Loup 2014 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 2 records from Neue Milbenarten aus Kärnten. 165 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 163 records from Dinoflagellate cysts of ODP Hole 189-1172D. 57 records from CSIRO Yellow Box Fragmentation Project. 673 records from Planktic foraminifera abundance of Hole 45-395. 62258 records from Entomology Collection at the Natural History Museum of Utah. 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 5460 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 84374 records from ALCB - Herbário Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 9 records from Herbarium specimens of Limoges university (LIMO). 3750 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 59422 records from Fish specimens of Kagoshima University Museum. 26 records from (Table T8) Occurrence of Neogloboquadrina pachyderma in ODP Hole 178-1098C. 112 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 3811 records from UTEP Invertebrates (Arctos). 59 records from Schulteich Freie Waldorfschule Darmstadt. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 10 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 684 records from Inventario de Flora de la Reserva Forestal Protectora Regional Cuchillas del Tigre, El Calón y La Osa. Municipios de San Francisco y Sonsón-Antioquia.. 163 records from Relative abundance of coccosphere-units at site GIK23414. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 12 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 4 records from Planktic foraminifera abundance of Hole 19-191A. 22052 records from CNIN/Abejas de México/Apoidea. 113 records from Foto trampeo al interior de las áreas del Banco de Hábitat del Meta de Terrasos. 1331 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 1303 records from Flora útil del Municipio de la Huerta, Jalisco. 3569 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 91 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 834 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 884 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 2067 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 159 records from Total foraminifera counts of multinet M36/6_MSN1196. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 10 records from Ostracod species in Oligocene sediments of core CRP-3. 15 records from Nannofossil abundance of Hole 10-93. 2194 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 4 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 7 records from Analyses of the recent components of sediment core PS1277-1. 352 records from Nannofossil abundance of Hole 60-458. 3466 records from MEXU/Leguminosae. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 1097 records from Planktic foraminifera counts of sediment core RC08-49. 32 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 235 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 509 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 4 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 58 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 1128 records from marine sediment metagenome Metagenome. 561 records from Range table from benthic foraminifers in ODP Hole 146-889A. 3769 records from Microbial ecology of archaeal community in sediment from adjacent waters of Rushan Bay. 1966 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 371 records from Bannwald Burghauser Forst. 9 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 21163 records from SEWBReC Bees, Wasps and Ants (South East Wales). 13 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 80 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 2127 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 10 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 154 records from Sorensen distance for herbivores. 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 111 records from Total foraminifera counts of multinet M33/1_MSN1029. 118 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 4 records from New species of Moluccan trichaline net-winged beetles, with remarks on the phylogenetic position and distribution of Schizotrichalus (Coleoptera: Lycidae: Metriorrhynchinae). 20520 records from University of Guam Insect Collection. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 832 records from Benthic foraminifera and algae abundance of Hole 81-552A. 11565 records from National Botanic Garden Belgium - Myxomycetes. 395 records from Planktic foraminifera abundance of Hole 32-310. 26 records from Dinoflagellate abundance of Hole 81-554. 3 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 516 records from Museu de Ciències Naturals de Barcelona: BGJBB. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 109 records from Nannofossil abundance of Hole 24-232. 177 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 11424 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 1340 records from Plasm bearing foraminifera counts during METEOR cruise M36/5. 1189 records from UWIZM Molluscs. 26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 56 records from Plasm bearing foraminifera counts of multinet M12/3_MSN562. 4083 records from MCP-Aves - Coleção de Aves. 265 records from Nannofossil abundance of Hole 36-329. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 149 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 104 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 115 records from Range table from planktonic foraminifers in ODP Hole 155-942C. 371 records from orthopteracollections-nhmj-ioj. 778 records from Bird specimens of Saitama Museum of Natural History. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 6 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 413 records from (Fig. 5) Sea-surface temperature reconstructions of sediment core MD99-2304. 3 records from Collections of Bioklass, school #179, Moscow. 22662 records from Microbial community structure and dynamics in the oxygen minimum zone of the Northeast subarctic Pacific Ocean. 256 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 625 records from Mycology collection, Norwegian Forest and Landscape Institute. 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 988 records from flower availability 2008 Alb-korrigiert. 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 2808 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 13 records from Dinoflagellate abundance of Hole 14-144. 23 records from Range table from planktonic foraminifers in ODP Hole 144-874B. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 35 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 34 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 235 records from Range table from benthic foraminifers in ODP Hole 161-974B. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 173 records from UWIZM Anoles. 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 7 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 444 records from Pollen analysis of sediment profile TR0 from Truennensee. 2451 records from Macrobenthos Chukchi Sea, 1986. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 12 records from Art´n Vielfalt im Kinderwald. 263 records from Planktic foraminifera counts of sediment core V14-77. 10 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 14 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 3800 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 302 records from UF Environmental Archaeology Tick Island Zooarchaeological Data. 251819 records from Phase 2 Lowland Grassland Survey of Wales. 385 records from Invasive Non-Native Species, Outer Hebrides. 16 records from Benthic macrofauna abundance of sediment core 13077-093. 1436 records from Naturalis Biodiversity Center (NL) - Crustacea. 60 records from Amphibian and Reptilian (KIEE-AR). 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 21 records from Brown algae specimens of Komatsu City Museum. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 325 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 78 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 420 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 1166 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 645 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 1285805 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 413272 records from DATAVES. 686 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 8 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1994-D2. 9145 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 742 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 465 records from The Broward College Insect Collection. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 7 records from Planktic foraminifera abundance of Hole 53-418B. 14 records from Berea College, Ralph L. Thompson Herbarium. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 424 records from Distribution of nanoplankton at trap WR2. 1406 records from (Figure 6) Dinoflagellate cyst measured on sediment core AI07-12G. 13624 records from Ecosphère_2017_12_18. 11 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 151854 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 794 records from Isle of Wight non-native invasive species. 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 581 records from Floristic records in the Moscow and Novgorod regions. 17 records from Marine metagenome ICM_AGW. 517 records from Weber State University Herbarium. 4 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 882 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 61 records from pangolin and pangolin products seized by the customs and pangolin public aided record from 2010 to 2019. 931 records from South American Antarctic Marine Biodiversity Literature. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 103 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 36 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 49 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 960 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 308 records from Naturmiljø Bergensbanen 2015 (project number 616033). 22 records from Ostracoda abundance of Hole 24-238. 17 records from Thirteen new records of ferns from Brazil. 4 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 15 records from Meiofauna abundance in sediment core 54301-010. 713 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 435 records from Marine metagenome ICM_AWP. 141 records from Collection Hydrozoa - ZSM München. 3557 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 4 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 121 records from Foraminifera abundance of sediment core IN68-28. 9057 records from NE Scotland other invertebrate records 1800-2010. 152 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 21 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 25 records from Base de données en ligne d'observations naturalistes de mammifères marins. GEPOG & LPO. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 6331 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 5 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 7 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 632 records from 2019_NSMK_PL. 558 records from Foraminifera abundance of Hole 74-526A. 267 records from Dinoflagellate abundance of Hole 81-555. 48 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 725 records from Relative abundance of Neogene nannofossils at ODP Site 165-998 from the Caribbean. 1696 records from Herbier National de Guinée (HNG). 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 651 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 456 records from EDIT - ATBI in Gemer area (Slovakia). 8 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 22113 records from Global compendium of Aedes albopictus occurrence. 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 88 records from Teich Berlin Wuhlheide. 186 records from Nannofossil abundance of Hole 27-259. 66 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 5 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 112 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 152 records from AKG-Gelände (Bensheim). 237 records from Planktic foraminifera abundance of Hole 21-207. 12 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 16 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 23 records from Benthic foraminifera abundance of Hole 93-603. 1 records from Occurrence of mammalia relicts at site Raagelund. 3 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 3983 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 18 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 84 records from Ostracoda abundance of Hole 48-403. 354 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 10699 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 1121 records from Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea). 20004 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 94 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 478 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 31 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 728 records from Planktic foraminifera counts of sediment core V27-178. 243 records from Antarctic Amphipoda. 210 records from Lebensraum Gesamtschule (Langerwehe). 425 records from Foraminifera abundance of Hole 64-481. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 2905 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-9. 76 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 905 records from Coléoptères Silphidés du département du Loiret. 2243 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 18 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 71 records from Occurrence of mammalia relicts at site Pestera Bursucilor. 308 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 123 records from Total foraminifera counts of multinet M21/2_MSN648. 2300 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 31152 records from Effects of Fecal Input, Environmental Conditions, and Environmental Sources on Enterococci Concentrations in an Estuarine Ecosystem. 3 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 2380 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 177 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 16 records from Hazel Dormouse in Ireland. 106 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 285 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 7 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 123 records from Total foraminifera counts of multinet M21/4_MSN694. 642 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 399 records from Planktic foraminifera abundance of Hole 14-142. 39329 records from Insects, Outer Hebrides. 2 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 46 records from An der Ohm, (Wettsaasen). 49 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 149 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 68 records from Nannofossil abundance of Hole 73-521A. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1276-1. 2419 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 3 records from Range table from planktonic foraminifers in ODP Hole 169-1038E. 13527 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 10 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 91 records from Radiolaria assemblage in sediment core GIK23400-3. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 701 records from Range table from benthic foraminifers in ODP Hole 151-913B. 216 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 1 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 73 records from Rhopalocères du PNR Périgord Limousin au 15/10/2015. 1739 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 1985 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 31457 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 124 records from Kirkliston Range stream monitoring. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 3 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 2 records from A new species of rheophilic cyprinid fish (Teleostei: Cyprinidae) from the Brahmaputra Basin, northeast India. 10611 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 2 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 16838 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 69319 records from Données de l'Observatoire de la Faune de Bourgogne. 46 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 1168 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 1930 records from Fungi of parks, forests and reserves of New Jersey, 2018. 1354 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 5 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 539 records from Phenological Center - Birds (Murmansk). 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 100 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 1208 records from Microbial diversity studies of Arabian Sea sediment. 18 records from Sarcodine counts and carbon biomass at station TT012_5-PMOC5. 185 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 6466 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 309 records from Echinoderms from the Seaflower Biosphere Reserve. 280 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 73 records from (Appendix A) Sea surface temperture reconstruction for ODP Hole 117-723A. 218 records from Nannofossil abundance of Hole 49-408. 24 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 11 records from Analyses of the recent components of sediment core PS1011-1. 368 records from Biological Recording in Scotland - Bumblebee Survey. 142881 records from Allan Herbarium (CHR). 51140 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 14275 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 26 records from MVZ Herp Observations (Arctos). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 323 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 265 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1244-2. 1 records from A new Portholefish of the genus Diplophos (Stomiiformes: Gonostomatidae) from the western Pacific Ocean. 6 records from Foraminifera abundance of Hole 58-442. 1 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 253 records from Données naturalistes d'Olivier LAURENT. 22728 records from Restauración y conservación de Isla Guadalupe. 407 records from (Table 2) Species composition of algae and cyanobacteria encountered in plankton of the Large Aral Sea on June 2-8, 2008. 5044 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 98 records from Warnowtal (Rostock). 930 records from (Table 2) Distribution of benthic foraminifera on sediment core PS2138-1. 124 records from Chronicle of Nature - Phenology of Insects of Baikalsky State Nature Biosphere Reserve. 6 records from Wuhle - Brücke / B1. 26 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 7071 records from Marie-Victorin Herbarium (MT) - Bryophytes. 462 records from Relative abundance of dead benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 4). 318 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 2 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 202122 records from National Benthic Inventory. 16 records from Phenological Center - Fishes (Murmansk). 5 records from (Table 2) Biomass of cysts and active infusoria in waters of the Peru coast area. 181 records from Dinoflagellate cysts from sediment core PS1295-4. 111 records from BIRDRACE Die Wendehälse. 88 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 177 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 3 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 1021 records from Phytoplankton abundance and species composition in the Gulf of Naples and the Gulf Salerno in November 1985. 186 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 8332 records from Scotland Otter Survey Database. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 1652 records from Utah State University, Intermountain Herbarium. 351600 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 1602 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 922 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 186 records from Benthic foraminifera and algae abundance of Hole 81-554. 42 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 64805 records from CAS Entomology (ENT). 24 records from Range table from benthic foraminifers in ODP Hole 178-1103A. 6085 records from Naturalis Biodiversity Center (NL) - Pisces. 216664 records from Carnet B Lorraine. 27 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 480 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in East Atlantic surface sediments off Senegal and Gambia (Table 1). 451 records from Counting of benthic foraminifera of ODP Hole 182-1132B. 5 records from Nannofossil abundance of Hole 16-157A. 60 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 735 records from Range table from planktonic foraminifers in ODP Hole 155-938A. 81 records from Kystfuruskoger i Tysnes og Fusa. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 29 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 91 records from Diatom abundance of Hole 95-613. 8 records from Die Bachspezies 2008/2009. 2364 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 73 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 3 records from Results of palynological analysis of Hole 302-M0004C. 45140 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 68 records from Streuobstwiese. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 23 records from Abundance of benthos infauna at station GIK23042-2. 4947 records from SIM-Fungal records compiled by Joan Montón. 747025 records from Western Australian Museum provider for OZCAM. 1152 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 197 records from ABC_Event data recorded on a day trip to Mongolwe and Chikala Hills Forest Reserve, Machinga District. 663 records from Benthic foraminifera counts of sediment core GIK23352-3. 3983 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 419 records from Mamíferos voladores y no voladores del suroccidente colombiano. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 49 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 2782021 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 749 records from (Appendix Table 3) Relative abundances of planktonic foraminiferal species in sediment core MD01-2390. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 164 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 33 records from Waldstück am Schullandheim Bad Bederkesa. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 5205 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1461 records from M. Gollop Collection. 334 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 1 records from Données naturalistes d'Olivier DELZONS. 218 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 68 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 164 records from Schulhof Gymnasium Hürth Bonnstrasse. 174 records from BIRDRACE Bon(n)apartemöwen. 10 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 14069 records from Midden-Limburg Fish Ponds Survey. 44367 records from Herbarium Senckenbergianum (FR) - Fungi. 1994 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 6478 records from National System of Protected Areas in Poland - Animals. 170 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 240 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 5 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 238 records from Vegetación asociada a la ciénaga de Bete, municipio del Medio Atrato, Chocó 2008. 158 records from Planktic foraminifera counts at CTD station PS55/063. 2829 records from (Figure 3) Stratigraphic distribution of planktonic foraminifera in the Neogene of ODP Hole 122-761B. 4193 records from Leicestershire and Rutland Aculeate Records. 177 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 2144 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 10110 records from Suivi Temporel des Libellules (STELI). 1 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 2712343 records from First Bird Atlas. 661 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 2 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 2 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 1 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 1 records from Reptilia ZMK. 5406 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 46337 records from University of Ghana - Ghana Herbarium. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 1911 records from Pollen profile RAC20, Lake Racou, France. 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 2807 records from Natura 2000 Vallée de la Seille. 591 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 2. 10192 records from Inventario de Hymenóptera; parasítica en México. 19066 records from IMPACT OF SAHARAN DUST DEPOSITION ON BACTERIOPLANKTON IN MARINE SURFACE WATER. 378 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 63085 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 3 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 8561 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1798 records from 3Soil16S. 1187 records from (Table 15) Distribution of planktonic foraminifers in ODP Hole 108-666A. 67 records from Planktic foraminifera abundance of Hole 9-76. 4126 records from (Table 4) Percentages of planktonic foraminiferal taxa from the 214 surface-sediment samples from the South China Sea and the western Pacific. 715 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 76 records from BIRDRACE Nachtigallen. 68 records from Nannofossil abundance of Hole 24-233A. 1573 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 61 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 1284 records from ConDidact Citizen Science Surveys - Amphibians 2007. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 55 records from Dinoflagellate abundance of Hole 28-274. 49 records from Total foraminifera counts of multinet FCA97C_MSN1345. 96 records from Données naturalistes (Rhopalocères et Zygènes) de Jude LOCK (indépendant). 119 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 50 records from Occurrence of mammalia relicts at site Biedermann. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 414 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 23138 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 676 records from Lucanidae. 27670 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 495 records from Planktic foraminifera counts of sediment core A15-558. 276 records from Birds Specimens of Akita Prefectural Museum. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 19 records from Données naturalistes de LE GLOANEC Vincent. 57451 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-64, 1974-5. 370 records from Size of planktic foraminifera at CTD station PS55/051. 41 records from MSUM Ichthyology and Herpetology Collections. 10 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 869 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 7122 records from Whale catches in the Southern Ocean. 363 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 16 records from Benthic macrofauna abundance of sediment core 13200-008. 1 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 31014 records from River Biologists' Database (EPA). 77073 records from CABI Africa Invasive and Alien Species data. 7504 records from Eurobodalla Regional Botanic Gardens. 1650 records from Great Eastern Ranges - Slopes to Summit. 75 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 75 records from Phytoplankton abundance at station Rigel_1_2005-02 in Febraury 2005, Chipana, Chile. 191294 records from Tiroler Landesmuseum Ferdinandeum. 91 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 1192 records from Pollen profile from a swamp at Seelohe, Fichtelgebirge, Germany. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 8851 records from Odonata records from RSPB Reserves 1970-2009. 1031 records from Données supplémentaires Atlas des Mammifères marins. 9 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 85 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 130 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 18 records from Anfibios presentes en el Cerro Jánano. 1715185 records from NBIS Records to December 2016. 149 records from Abundance of radiolaria at station UT99-23-2. 27 records from Planktic foraminifera abundance of Hole 51-417B. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 2676 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 375 records from (Appendix E) Stable carbon and oxygen isotope composition of Globigerinoides sacculifera of ODP Hole 121-758B. 2859 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 550 records from Radiolaria assemblage in sediment core GIK23414-6. 386 records from (Table 3) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704A. 320 records from Myxomycetes collection of the University of Eastern Finland. 321633 records from Seasearch Marine Surveys in England. 53 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 38 records from Planktic foraminifera abundance of Hole 84-566C. 308 records from Tejidos de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 2963 records from Collection Trichoptera - SMF. 162 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 16 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 115 records from Nannofossil abundance of Hole 1-3. 132 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 130 records from Abundances of dinoflagellate cysts in sediment trap MST-9 (Appendix 1). 255 records from Occurrence of mammalia relicts at site Raj Cave. 100 records from Nannofossil abundance of Hole 6-55. 3740 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 798 records from Planktic foraminifera abundance of Hole 27-262. 107742 records from Arizona State University Hasbrouck Insect Collection. 3776 records from (Figure 5) Range chart of selected dinocysts and acritarchs of ODP Hole 104-642A. 39 records from Planktic foraminifera abundance of Hole 27-260. 2536 records from Invasive Alien Species Occurrence in Ghana. 63364 records from CCAMLR historic KRILL. 89 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 3585 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 240 records from Chironomid remains in the sediment sequence of Site PG1212. 1480 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 3379 records from Lista florística de la Costa Grande del estado de Guerrero. 13 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG.. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 87901 records from MDFRC macroinvertebrate survey. 62 records from Amtsrain Apolda-Zottelstedt. 76 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 179 records from (Table 9) Relative abundance of calcareous nannofossil species across the Cretaceous/Paleocene boundary at ODP Hole 120-750A. 63255 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 53 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 57 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 230 records from (Table 2) Range chart for planktonic foraminifers from ODP Hole 111-677B. 108 records from Nannofossil abundance of Hole 31-299. 151 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 9476 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 4853 records from Inventaire des espèces végétales du sous bois des plantations de Teck de la forêt naturelle de la Lama. 40 records from Planktic foraminifera abundance of Hole 14-137. 2321 records from UWYMV Bird Collection (Arctos). 1609763 records from Hatikka Observation Database. 62 records from Range table from planktonic foraminifers in ODP Hole 183-1139A. 186260 records from inatura - Erlebnis Naturschau Dornbirn. 16 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 386 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 42 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 1162253 records from PlutoF platform observations. 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 1500 records from (Table 2) Stratigraphic occurrence of selected diatom species from DSDP Hole 12-112. 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 136 records from Total foraminifera counts of multinet M21/6_MSN784. 5 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 8 records from Benthic macrofauna abundance of sediment core 13078-015. 84 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 129 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 95 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 11030 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 238 records from Données Mammifères marins Aquasearch - Dauphin Passion. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 1275 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 2 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 1249 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 10075 records from Nematoda of Costa Rica (INBio). 45 records from Nannofossil abundance of Hole 10-89. 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 177 records from Nannofossil abundance of Hole 30-285A. 23648 records from WTSWW Data: All Taxa (West Wales). 614 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 213 records from Pollen record of profile 3TZ. 421246 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 192 records from "Ahrschleife bei Altenahr". 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 367287 records from South Australian Museum Australia provider for OZCAM. 2 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 35 records from Plasm bearing foraminifera counts from multinet M32/3_MSN957. 5 records from Coccolith counts of multinet M32/5_MSN981. 100 records from Brock University Herbarium (BU). 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 220 records from (Table 1) Distribution of planktonic foraminifers in ODP Hole 126-787B. 214 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1246-4. 7115 records from Whicher Scarp Flora Survey. 69 records from Unter hellen Zinnen und finsteren Grotten. 16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 1003 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 10 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 10 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 134 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 6446 records from Modernisation des ZNIEFF du PnrL. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 129 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0011B. 20 records from Occurrence of mammalia relicts at site Niederlehme. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 2366 records from Cryoconite sediments Targeted Locus (Loci). 86 records from UWIZM Cnidarians. 17 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 80 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 148842 records from Tasmanian Museum and Art Gallery provider for OZCAM. 14302 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 938 records from TTRS Mammals. 148 records from Occurrence of mammalia relicts at site Veternica. 6 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 6 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 4579 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 2 records from Benthic foraminifera abundance of Hole 42-376. 618 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 1545 records from NatureMap Calcrete Survey. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 452 records from Benthic foraminifera counts of sediment core PS1852-2. 6357 records from Distribution of foraminifera of sediment core GIK23258-2. 2606 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 1 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 5 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 521 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 38 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 49035 records from University of Minnesota Insect Collection. 16 records from Insect Collections of Okomu National Park- Nigeria. 235 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 412 records from Heinersdorfer Sumpfwiese. 133650 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 279489 records from ARABEL - Arachnologia Belgica. 8 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 8 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 22680 records from Arctic Species Trend Index (ASTI) : Marine. 53 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 3332 records from Dead benthic foraminifera of surface sediment of the Persian Gulf (Table 2). 33416 records from Wolli Creek Preservation Society Bird Survey. 348 records from Antarctic pycnogonids. 553 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 60926 records from MLZ Bird Collection (Arctos). 63 records from Inventaire des espèces végétales de la vallée de Gounti Yéna (Niamey). 5 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 14 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 126 records from Naturschutzgebiet Müchelholz (Mücheln). 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 166 records from Wiese am Waldrand (Gurtweil). 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 148143 records from ImageDOP Bentic Video Annotations in the Faial-Pico Channel in 2011. 351 records from UWYMV Herpetology Collection (Arctos). 3 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 4880 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Site 198-1213. 7887 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 5538 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 88 records from Total foraminifera counts from M35/1_MSN1065. 2781 records from Marine Turtles. 196 records from Foraminifera abundance of Hole 33-317A. 670 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 120 records from Total foraminifera counts of multinet M21/2_MSN650. 6 records from Microzooplankton abundance and biomass at station NBP97-03-03-5. 6 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 159 records from Nannofossil abundance of Hole 67-499B. 3933 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 463 records from Foraminifera abundance of sediment core IN68-9. 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 6 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 6661 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 417 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 4 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 178 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron. 101 records from Naturgrundstück (Eutin). 10766 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 4230 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene of ODP Hole 105-645E (Table 1). 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 14 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 1625 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 20 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 2988 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 12 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 93662 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 1 records from Occurrence of mammalia relicts at site High Furlong. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 36 records from University of Sindh Jamshoro Herbarium. 2924 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 58 records from Occurrence of mammalia relicts at site la Grotte des Eglises. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 19 records from Marine metagenome ICM_CNE. 1140 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 1 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 227 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 128 records from Faunal assemblage of sediment core TR149-32. 904 records from Nannofossil abundance of Hole 15-149. 62 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 3 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 1913 records from Registros Primates Neotropicales Convocatoria APC. 631 records from Anammox bacteria in sediment cores of Daya Bay, China. 13 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 134 records from Pollen record of profile 3TZ2. 134 records from Planktic foraminifera counts at CTD station PS55/079-1. 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 111 records from Birdrace-Uhulogen-Lippe. 8 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 12 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 7128 records from La familia Asclepiadaceae en México. 4 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 8 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 311 records from Benthic foraminifera abundance of Hole 41-366A. 26 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 373 records from Otter survey of Ireland 2004 & 2005. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 9968 records from (Table T7) Calcareous nannofossil stratigraphy of ODP Hole 198-1210B. 111099 records from Suivi Temporel des Rhopalocères de France (STERF). 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 15 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 23 records from Australian Museum Ichthyology - 2012 Inscription Point. 2 records from Sinibotia lani, a new species of botiid loach (Teleostei: Botiidae) from Guangxi, China. 144 records from Total foraminifera counts of multinet POS247/2_MSN1386. 411 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 153 records from Planktic foraminifera abundance of Hole 18-181. 198 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 1 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 16922 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 3444 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 237 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 2 records from Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak. 1004 records from Dead benthic foraminifera of surface sediments from the East Atlantic continental margin off Portugal (Table 5 & 7). 16 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-11-5. 319 records from Pollen data of trap CB4. 1481 records from Leicestershire and Rutland Mature trees Inventory 2011. 1 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 11 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0004C. 16 records from Valentin Moser Bats. 807 records from Planktonic bacterial communities in the arctic Canada Basin and Kongsfjorden. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 52443 records from Extracellular DNA marine sediment Targeted Locus (Loci). 54 records from Phytoplankton abundance at station Rigel_5_2005-02 in Febraury 2005, Chipana, Chile. 2 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 285 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 136 records from Abundance of planktic foraminifera at CTD station PS55/080-1. 384 records from "Schwarzwassertal" bei Pobershau. 1932 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 5 records from Microfossil abundance of Hole 21-208. 217 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 928 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 1 records from Occurrence of mammalia relicts at site Ejstrup. 2340 records from marine metagenome Targeted Locus (Loci). 24493 records from Plan de vertebrados de la Patagonia. 1170 records from Springtales from lichen communities at Kollåsen in Norway. 5 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 67 records from Planktic foraminifera distribution of sediment core TRI171-27. 4515 records from Distribution of planktic foraminifera of sediment core M35003-4. 1108 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 3 records from Occurrence of mammalia relicts at site Igstadt I. 268 records from Planktic foraminifera abundance of Hole 22-217. 304444 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 132 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 975 records from Danielsberg (Mölltal, Kärnten). 199 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 8 records from Nannofossil abundance of Hole 39-353A. 16985 records from LPO_PACA_2017_12_18. 95 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 318 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 3877 records from (Table 3) Relative abundance of benthic foraminifera in sediment profile HUD84-030-04. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 661 records from Targeting a portion of central European spider diversity for permanent preservation. 43 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 10907 records from Census of species recorded during phytosociological surveys in Benin. 165 records from Nannofossil abundance of Hole 3-15. 6977 records from 2019_NSMK_PL_2. 1887 records from Foreign plant germplasm collections in Ghana. 2073 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 1558 records from (Table 3) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-707A. 64 records from (Table 4) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the upper part of the Calabianca section. 439 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 6579 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 6556 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 1 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 1 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 41553 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 390 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 55 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 99 records from Dorfrand Mauderode. 411 records from SuLaMa reptile survey I 2012. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 61 records from Shrews of Poland. 152 records from (Table 2) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-543. 9 records from Nannofossil abundance of Hole 2-11. 2 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 17755 records from K-State Museum of Entomological and Prairie Arthropod Research. 4 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 269 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0012A. 2274 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 15 records from Nannofossil abundance of Hole 6-48B. 181715 records from Marine benthic dataset (version 1) commissioned by UKOOA. 277 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 5229 records from European Moth Nights. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 81 records from Range table from planktonic foraminifers in ODP Hole 177-1089D. 1825 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 946 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 67938 records from Microbial diversity in the Benguela coastal upwelling system as derived from 16S rRNA sequencing and RNA Stable Isotope Probing (SIP). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 931 records from Données naturalistes de Mathilde DUSACQ. 2068 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 1 records from MfN - Micropaleontology. 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 296 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 1036 records from BUND - Dassower See (Lübeck/Dassow). 4 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 346 records from Birds and plant species near Petushki town (Vladimir region). 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 2 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 984 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 54016 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 4 records from Sächsische Schweiz (Wehlener Gebiet). 113 records from Appendicularia abundance of station M9_A near the Great Meteor Bank, Northeast Atlantic (Table 1). 1003 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 356 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 6067 records from Arthur Chapman Observations. 571 records from Cuxhavener Küstenheiden. 651 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 186 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB02 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 13542 records from Collection Pisces SMF. 1 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 12202 records from Pelagic Gulf of Mexico Targeted loci environmental. 3 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 1131 records from MEXU/Tipos de plantas vasculares. 30 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 1642 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 442 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 4 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 4 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 242 records from Landschaftspflegehof (Berlin). 10 records from Bachpatenschaft Beeke. 341 records from SPC CoFish Invertebrates Observations Niue 2005. 84 records from Total foraminifera counts from M35/1_MSN1051. 16 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 5366 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 91 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 390 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 167 records from Artenvielfalt auf den Elbwiesen (Dessau). 1009 records from Données naturalistes de Daniel PAVON. 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 3 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 201 records from Total foraminifera counts of multinet M21/1_MSN606. 2917 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 694 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-127. 17 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 250684 records from Estonian Nature Observations Database. 14 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 38375 records from Botanical Museum, Copenhagen, Mycology Herbarium. 589 records from Birds (NMNO-BI). 1095 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 11305 records from NCSM Mammals Collection. 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 24 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 770 records from Nivå Bay species list, Zealand, Denmark. 814 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 91645 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 7 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 164135 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 87 records from VFD-H: Heidenrod: Pferdeweide Mürth. 56 records from Total foraminifera counts of multinet M21/4_MSN720. 12413 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 104 records from Range table from benthic foraminifers in ODP Hole 172-1059B. 426 records from Données du Centre de la mer de Biarritz. 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 11 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 5 records from A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus. 2 records from A new species of Yllenus Simon, 1868 from northern India (Araneae, Salticidae). 92 records from Nottekanal, Klasse 7 - 10. 54 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 597 records from Percentages of planktonic foraminifera species in sediment core V30-40. 311 records from Nannofossil abundance of Hole 37-333. 4845 records from Inventaire des Mollusques Sphaeriidae de France. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 53 records from (Table 1) Fauna composition of the community of Amphiodia urtica - Nephtys ferruginea in bottom sediments from the central part of the shelf in the California upwelling zone. 3030 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 78 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1389. 2004 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 1409 records from Diatom assamblage in samples from sediment trap OG5. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 3919 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 6679 records from Données issues du dispositif de Biosurveillance des Retombées Atmosphériques Métalliques par les Mousses (BRAMM). 50 records from Flora und Fauna im Brexbachtal. 898985 records from MICROBIS database. 190 records from Herpetofauna laguna El Tinije. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 14619 records from Ontario Breeding Bird Atlas 1981-1985. 123 records from Birdrace-Professorenteam-Münster. 6927 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 3399 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 3 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 391 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 248680 records from Swiss National Orthoptera Databank. 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 131 records from Planktic foraminifera counts at CTD station PS55/083-1. 273 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 30091 records from BIOWIDE eDNA Fungi dataset. 45367 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 134 records from Pollen profile II/B at Krumbach, Germany. 35090 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 51 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 31 records from Nationalpark Harz Schul-AG Braunlage. 12844 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 594 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 1067 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 140 records from Inventaire de la faune aviaire et de l'Ichtyofaune de la mare de l'Abarkaizé et des Oiseaux de Dan Saga. 572 records from NEW-1. 4 records from Description of a new species of deep-water snake eel, Ophichthus mccoskeri (Ophichthidae: Ophichthinae) from Andaman Sea, India. 38 records from Was lebt in der Brutzwiese?. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 61 records from Phytoplankton abundance at station Sechin_2003-07-15_2, Casma, Peru. 2 records from Nannofossil abundance of Hole 4-26A. 96 records from Planktic foraminifera abundance of Hole 22-212. 28 records from Biodiversity Surveys, South-east Arnhem Land. 138472 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 1 records from A new species of Pyrrhosphodrus (Hemiptera: Heteroptera: Reduviidae) from the Caatinga ecosystem in Brazil, with notes on the genus. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 287 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 39 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 120 records from Tejidos asociados al estado de conservación y riesgo de extinción del ensamblaje de anfibios de tres páramos colombianos. 5809 records from (Table 1) Dinoflagellate range chart of ODP Hole 120-748C. 86 records from Données naturalistes de Pierre-Alexis RAULT. 60 records from Wichita State University Collection. 376028 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 151 records from Levantamento da vegetação arbustiva do Parque Nacional do Jaú. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 8158 records from Dark ocean microbial diversity. 106 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 10 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 327 records from pbzt_insect_biodiversity. 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 6445 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 9743 records from marine sediment metagenome Raw sequence reads. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 287 records from Nannofossil abundance of Hole 66-488. 40 records from Heavy minerals of sediment core PL94-64. 5 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 131978 records from Amphibiens et Reptiles de France (Enquête 2). 2131 records from Dolichopodidae of Portugal - dataset 2009-2018. 3320 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 1450 records from Données naturalistes d'Alain BERLY. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 27676 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 221 records from (Table 6) Ostracod assemblages of sediment core 9409. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 368 records from Ring ouzel national sample survey in the UK in 1999. 2240 records from (Figure 7) Distribution chart of benthic foraminifers in ODP Site 126-793. 1698 records from Red-throated diver national surveys in Scotland - raw data. 215 records from (Table S2) Nannofossil abundances at DSDP Hole 86-577A. 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 64 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 14846 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 638313 records from Données de la flore d’Alsace (SBA). 498 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 1 records from Two new Afrotropical genera of Scatopsidae (Diptera). 5046 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 696 records from the diversity of anammox bacteria in the subterranean estuary. 2 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 380 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 26185 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 51 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/009-2. 1153 records from Nannofossil abundance of Hole 17-167. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 166 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_3-CTD39. 2 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 4 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 2744 records from Distribution of major planktic foraminifer at Site 177-1090. 122 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 1925 records from Caracterización de la vegetación en una zona delimitada en Cumbitara, La Llanada, Policarpa y Los Andes Sotomayor (Nariño), como insumo para la identificación de oportunidades de conservación para la recuperación de los servicios ecosistémicos de bosque seco. 665 records from Planktic foraminifera counts of sediment core V04-8. 126 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 110511 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 7 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 12 records from Range table from planktonic foraminifers in ODP Hole 151-912A. 4644 records from (Table 10) Eocene-Oligocene diatom biostratigraphy of ODP Hole 120-748B. 10213 records from MfN - Fossil plants (Paleophytic). 4227 records from Données naturalistes de Loïc SALAUN. 1139 records from SWECO. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 1694 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 15860 records from EAC - Herbário Prisco Bezerra. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 2507 records from East Ayrshire Species Database. 2565 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 1200 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 9 records from Sarcodine counts and carbon biomass at station TT011_6-CTD71. 63 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 195 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 8697 records from Collection Crustacea - ZMB. 708 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 935 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 19 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 1 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 1 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 93 records from Plasm bearing foraminifera counts from multinet SO119_MSN1284. 36 records from Nannofossil abundance of Hole 25-249. 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 4536 records from (Table 3B) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572C and 85-572D. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 1 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 1249 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 100 records from Microzooplankton abundance measured on water bottle samples at station PS65/514-2. 143 records from Dermaptera in the icipe collection. 212 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 2344 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 25 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 29 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 32660 records from The national database for marine data (MADS). 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 31 records from Nannofossil abundance of Hole 9-82. 204 records from Foraminifera abundance of Hole 57-440A. 19 records from Description of lithologic section units of IODP Hole 325-M0035A. 4 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 2654 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 59 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 2327 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 6 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 102 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 288 records from Size of planktic foraminifera at CTD station M39/4_402CTD-55. 54 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction. 114 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 13 records from Warnowufer Groß Klein. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 253 records from NZCS Upper Tapanahony Expedition 1991. 307 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 22 records from Tanzanian Vertebrate Collection. 852 records from Phytoplankton abundance in surface water in November 1997, Pisco, Peru. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 3 records from DD_cyano Targeted loci environmental. 54 records from Anfibios y reptiles de la serranía las Quinchas, Boyacá - Proyecto Boyacá BIO. 5 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 2 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 96 records from Coleção de Nematoda do Museu Nacional - UFRJ. 6652 records from Inventory of plant species through Benin (West Africa). 551 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 4109 records from South Caribbean Diversity. 2 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 70 records from Total foraminifera counts of multinet M21/5_MSN731. 19 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 31885 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 1778 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 1123 records from Planktic foraminifera abundance of Hole 72-516F. 4 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 1 records from Benthic foraminifera abundance of Hole 96-624. 986 records from HDCF herbarium - Universidade Federal de Santa Maria - Herbário Virtual REFLORA. 5 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 11249 records from Heteroptera collections of SW Finland. 361 records from (Appendix 4, Table 4) Relative abundances of benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 9 records from Range table from planktonic foraminifers in ODP Hole 183-1136A. 517 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 18096 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 564 records from Atewa Range Forest Reserve Bryophytes dataset, Ghana. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 2621 records from Fungi specimens of Saitama Museum of Natural History. 1530 records from Pollen record of sediment core Bokanjacko Blato 1. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 7 records from Benthic hard-bottom communities abundance at X-Huinay, Comau Fjord, Chile, in 2010. 140 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 36 records from BIOMEO_2017_12_18. 211 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 841 records from Planktic foraminifera abundance of Hole 72-518. 518 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 33 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 11 records from Paracobitis abrishamchiani, a new crested loach from the southern Caspian Sea basin (Teleostei: Nemacheilidae). 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 3 records from A new species of Ninia (Serpentes: Dipsadidae) from Chocó-Magdalena biogeographical province, western Colombia. 602 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 14 records from Nemertini - SMF. 1190 records from Tracking data from a free-roaming female cheetah released into the Pilanesberg National Park, South Africa. 2931018 records from Eremaea. 14 records from Benthic foraminifera abundance of Hole 96-620. 86616 records from Marine Offshore Seabed Survey data held by JNCC. 100 records from Nanoplankton abundance at station GeoB2006-4. 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 3 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 1475 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 3238 records from Natural History Museum Rotterdam (NL) - Chordata collection. 65 records from Occurrence of mammalia relicts at site Sütto_6. 12 records from Mamíferos del municipio de Santa Bárbara, Santander - Proyecto Santander BIO. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 96508 records from Herbarium of Taiwan Forestry Research Institute. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 3 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 23 records from Ackerrain Plönhagen. 2 records from New Notophthiracarus species (Acarina, Oribatida, Phthiracaridae) and overview of the distribution of the genus in South Africa. 7019 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 242 records from Malawi-Histeridae-Biodiversity-Data. 1 records from Great Sippewissett Marsh Plot nirS Targeted Locus. 1438 records from Planktic foraminifera abundance of Hole 7-64. 4439 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 11001 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 1078 records from Pollen profile from Seminary School Basin. 25 records from Microzooplankton abundance and biomass at station TT043_4-1. 1 records from Schistura alboguttata, a new loach species of the family Nemacheilidae (Pisces: Cypriniformes) from the Pearl River basin in Guangxi, South China. 52 records from Benthic foraminifera and algae abundance of Hole 35-325. 2 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 313 records from BIRDRACE Gätkes Erben. 2990 records from (Table 13) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-715A. 3304 records from Benthos counted on dredged samples during Valdivia cruise VA53. 214 records from Total foraminifera counts of multinet M21/1_MSN608. 103 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 14997 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 5869 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 1882 records from Carabidae of the European North-East of Russia. 4011 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 1297 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 262 records from Variability of benthic Foraminifera north and south of the Denmark Strait. 6 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD63. 1057 records from Palynological analysis of sediment core GeoB9508-5. 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 2 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 25 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 131 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-56. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 6 records from Abundance of benthos infauna at station GIK23065-1. 27254 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 593 records from Flux data of NU2_trap (Table A1). 4 records from Planktic foraminifera abundance of Hole 17-166. 2712064 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 16 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 228 records from Bishop's University Insect Collection (BUIC). 5 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 24 records from ALTERECO_2017_12_18. 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 25 records from Chameleonfishes in Bangladesh: hipshot taxonomy, sibling species, elusive species, and limits of species delimitation (Teleostei: Badidae). 5350 records from Sediment metagenome. 491586 records from BioFokus. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 15255 records from Anymals+plants - Citizen Science Data. 17943 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 53 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 1 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 5494 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 8423 records from University Of Pretoria: Lacewing Database Project (1911-2015). 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 383 records from Nannofossil abundance of Hole 66-490. 3277 records from USAC Mammals Collection. 195 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100500. 1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 1 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 3350 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 515 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 733 records from (Table 14) Distribution of planktonic foraminifers in ODP Hole 108-665A. 50 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 168 records from Occurrence of mammalia relicts at site Geißenklösterle. 270 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 2350 records from Données naturalistes de Bernard Lalanne-Cassou. 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 1136 records from Nannofossil abundance of Hole 82-558A. 37 records from Planktic foraminifera counts of sediment core RC13-154. 1513 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 7 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 3327 records from BioGIS - Mammals - SPNI. 21 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 29520 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 90159 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 13 records from Diatom abundance of Hole 60-460. 23 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 18 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 917519 records from SEWBReC Birds (South East Wales). 861 records from (Table 1) Percentage of Coccolithus pelagicus vs. Reticulofenestra spp. of ODP Hole 120-747A. 216 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 50940 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 569 records from (App 2) Relative contents of benthic foraminifera species in Holocene sediments from Core ASV11-858-3. 807 records from Área Galeras - Monitoreo de Aves, 2016. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 141 records from Total foraminifera counts from multinet SO119_MSN1285. 163 records from Zostera noltei seagrass meadows spatial distribution at LTER site Ria de Aveiro lagoon in 2014. 395 records from Collection Echinodermata SMF. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 5883 records from MfN - Fossil vertebrates IV. 5020 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 22 records from The fishery ground near Alexandria. XVI. Cumacea, stomatopoda, leptostraca by Adolf Steuer (1938).Notes and Memoirs No 26.. 782 records from Planktic foraminifera abundance of Hole 42-372. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 32826 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 1607 records from MEXU/Flora de Oaxaca. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 6 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 2 records from Planktic foraminifera counts of multinet PS2616-5. 18 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2445-2. 4207 records from CASES2003_2004. 376 records from Digitalización y sistematización de las colecciones biológicas del INECOL. 39586 records from Fife Nature Records Centre combined dataset. 52 records from CHAS Botany Collection (Arctos). 203 records from Total foraminifera counts of multinet M21/1_MSN604. 10 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 3 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 822 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 54 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 272 records from BIRDRACE Niederlausitz-Team. 86 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 6755 records from Odonata de Veracruz. 1441 records from Planktic foraminifera abundance of Hole 18-173. 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 279 records from (Table 6) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-849B. 7653 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 364 records from Chronicle of Nature - Phenology of Birds of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 4421 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 1379 records from Composition of the coccolith flora in sediment core GeoB1710-3. 635 records from CG04_2017_12_18. 5 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 255 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 11 records from Collection Ephemeroptera - SMF. 33 records from Microzooplankton abundance and biomass at station TT045_15-2. 10397 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 3 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 97757 records from Denver Museum of Nature & Science - Entomology. 42 records from (Table 1) Abundance, wet biomass, and carbon biomass of all major groups of phytoplankton in the water column of the Kara Sea. 14557 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 441 records from Relative abundance of planktic foraminifera in sediment core RC08-39. 16506 records from Database for alien invasive plants occurrences in Germany. 18 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 66 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 1333 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 871 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 8313 records from 成龍溼地鳥類生態紀錄. 533 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 84 records from Benthic foraminifera abundance of Hole 84-566C. 704 records from (Table 17) Nannoplankton distribution in sediment core ANS3-T4. 1351 records from (Appendix B) Relative abundances of larger size planktonic foraminifera in latest Maastrichtian sediments of DSDP Hole 74-525A from Walvis Ridge, South Atlantic. 2462 records from Waarneming.nl (NL) - Great Grey Shrike Count 2011-2012. 3673 records from Spider (NSMK-SP). 3489 records from OUPR - Herbário "Professor José Badini". 15 records from Nannofossil abundance of Hole 58-442B. 57217 records from National Biodiversity Data Bank. Observation records, 1900-2014. 17 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 334 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 100 records from 20th century Betula pubescens ssp. czerepanovii tree- and forest lines in Norway. 3383 records from Planktic foraminifera abundance of Hole 23-219. 1571 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 849 records from CNAN/Scorpiones. 1 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 96 records from Total foraminifera counts of multinet M26/1_MSN845. 46 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 63-125 µm fraction. 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 462 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 6 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 6 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 1 records from A new species of Orthosiphon (Lamiaceae) from Angola. 424 records from Collection de C.C.H. Jongkind aux Monts Nimba. 2 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 458 records from Percentages of planktonic foraminifera species in sediment core V15-168. 4 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 2 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 8 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 4816 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 116 records from Nannofossil abundance of Hole 20-200. 907 records from Pollen profile Märchenwald B, Harz, Germany. 243 records from Thistles species and abundance. 61 records from Phytoplankton abundance at station Casma_2003-03-27_2, Casma, Peru. 115 records from On the absence of the Green-tailed Trainbearer Lesbia nuna (Trochilidae) from Venezuela: an analysis based on environmental niche modelling. 47 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 30-63 µm fraction. 2851 records from Northern Gulf of Mexico Hypoxia can Alter Sediment Communities of Nitrifying Archaea. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 1 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 38 records from Numbers and statistics of benthic foraminiferal Q-mode assemblages for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 2120 records from Flora vascular acuática de la cuenca del Río Tamesí. 379 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 57 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 12 records from A new genus and two new species of miniature clingfishes from temperate southern Australia (Teleostei, Gobiesocidae). 5664 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 753755 records from Inventaire National du Patrimoine Naturel : Oiseaux hivernants de France. 814 records from flower availability 2008 Hainich. 1854 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part III. 1 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 732 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 5 records from Two new nematode species of the genus Tobrilus Andrássy, 1959 (Nematoda, Triplonchida) from Lake Baikal, Russia. 1125 records from Données naturalistes de Stéphane ORIO. 702 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 8737 records from Andes to Amazon Biodiversity Program. 155303 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 21 records from Nannofossil abundance of Hole 3-22. 2 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 477 records from Coleção de Ictiologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZIUMCN-UNIVATES). 1305 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 3063 records from Données entomologiques sur la Réserve Naturelle de l’Étang Noir. (Seignosse, Landes). Bilan des études 2001 à 2009. 5406 records from Données Lépidoptères de l'Auvergne transmises par Pascal Peyrache.. 990 records from Bacterial communities from Thrombolites of Lake Sarmiento. 25253 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 8190 records from (Table 7) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-709C. 134 records from BIRDRACE Griffin Wood Warblers. 156 records from Deep-Sea holothurians (Echinodermata, Holothuroidea) of the Colombian Southern Caribbean Sea. 9 records from Planktic foraminifera abundance of Hole 94-611B. 1736 records from Relative abundance of planktic foraminifera in sediment core GeoB1312-2. 1 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 2 records from Microzooplankton abundance and biomass at station TT054_24-22. 76 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 915 records from Nannofossil abundance of Hole 30-286. 2476 records from Range table from benthic foraminifers in ODP Hole 154-929A. 5 records from A new species of Victrix Staudinger, 1879 from Kazakhstan (Lepidoptera, Noctuidae). 45 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Fannich Hills SSSI. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 39 records from Nannofossil abundance of Hole 7-63. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 61366 records from Derek Lott Coleoptera Dataset. 2 records from Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66). 78224 records from University of Tennessee Bryophyte Herbarium. 2662 records from PINK - Dragonfly (Odonata) monitoring for the permanent surveillance of coastal areas in Flanders, Belgium. 41 records from Planktic foraminifera counts of sediment core V28-128. 7646 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 70 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 490 records from Sequences obtained from two sponge genera (Hyrtios, Aiolochroia), one zoanthid (Palythoa), and marine sediments. Metagenome. 16924 records from Censo de ardeidas invernantes y nidificantes de la Comunidad Autónoma del País Vasco. 6541 records from Likona Invertebrates. 291 records from SuLaMa reptile survey 2013. 179 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 129368 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 167 records from Nannofossil abundance of Hole 7-62A. 3379 records from Amphibiens de Guyane. 182 records from Planktic foraminifera abundance of Hole 62-465. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 29 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5112-4. 9 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 30 records from Nannofossil abundance of Hole 9-82. 1186 records from Nannofossil abundance of Hole 75-530A. 24 records from Planktic foraminifera abundance of Hole 20-200A. 4 records from Collection Myriapoda - SNSD. 38 records from BB-Biodiversität a. 7248 records from DBRC Hemiptera species records 1969 to 2015. 1857 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 78612 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 1357 records from (Table 9) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-591B. 1868 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A. 25 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 3546 records from Dorset SW Pilot species dataset. 11 records from Benthic macrofauna abundance of sediment core 13077-087. 1914 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 324 records from (Table 2e) Nannofossil distribution chart of petroleum well Leeuwin-1. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 100 records from (Table 5) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the Lesches en Diois section. 320 records from Nannofossil abundance of Hole 24-237. 2080 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 13845 records from Cumbria Non Native Invasive Species. 1 records from Description of the male of Phoebe ornator (Tippmann, 1960) (Coleoptera: Cerambycidae: Lamiinae: Hemilophini), analysis of the species biogeography, and first observation of chromatic gender dimorphism in Hemilophini. 596 records from Lower Albian l'Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 1 records from Morphological and molecular analyses confirm the occurrence of two sympatric Lysmata shrimp (Crustacea, Decapoda) in the southwestern Atlantic. 47 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 319 records from SNH Invertebrate Site Condition Monitoring 2013/14: Cairngorms SSSI. 10 records from Description of a new species of Caridina (Crustacea: Decapoda: Atyidae) from two Micronesian islands (Guam and Babeldaob). 71 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2007. 177 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 371 records from Benthic foraminifera and algae abundance of Hole 81-554A. 1056 records from Diatom assamblage in samples from sediment trap OG4. 1854 records from Microbial diversity in shallow water hydrothermal sediments of Gueishan Island, Taiwan. 23 records from Landwehrbach. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 9781 records from CSIRO, fish surveys by the Soela, 1980s. 597 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 61 records from Alien Species in Poland - Plants. 931 records from Microfossil abundance of Hole 16-158. 406 records from Nannofossil abundance of Hole 78-543. 22771 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 1156 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 13 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 35 records from Total foraminifera counts of multinet FCA97C_MSN1339. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 28307 records from Bosque Mesófilo de Montaña de México. 56 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 22853 records from Données de Lépidoptères de Denis Vandromme. 37058 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 29 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 488 records from Planktic foraminifera distribution of sediment core SU81-07. 1942 records from Collection ornithologique A. Maës. 31 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 926 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 1 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 46 records from Mammal specimens of Komatsu City Museum. 12 records from Urban Barcode Project - Fungi. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 270 records from ACT and Southern Tablelands Weed Spotter. 1 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 41 records from Örtzemündung (Stedden). 1938 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 30233 records from National Stag Beetle Surveys (Great Stag Hunts). 609 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 8 records from Abundance and carbon biomass of phytoplankton at station TT007_4-CTD48. 363 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 170543 records from England Non Native Species records 1965 to 2017. 134 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 18 records from Nannofossil abundance of Hole 3-18. 1 records from The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae). 8 records from Microzooplankton abundance and biomass at station TT050_17-4. 1 records from The discovery of Euryrhynchidae (Crustacea: Decapoda) in India, with the description of a new genus and species. 225 records from L’évaluation environnementale du projet du barrage de la retenue d'eau, de Guinea Alumina corporation à sangaredi, Boké (CESP2016-022). 7 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 2898 records from DBL_Life. 4 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 3350 records from Reef Check in Taiwan 台灣珊瑚礁體檢. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 836 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 195 records from Pedestrian mammals census in W National Park. 1 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 29741 records from BLS Rare and Threatened Lichen Records: England. 8 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 145 records from Gronau - auf der Suche nach dem Neunauge. 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 95 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 1123 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 116 records from (Table 4) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-599. 1 records from Discovery of the transantarctic distribution of the genus Metanteon Olmi (Hymenoptera: Dryinidae), with description of a new species from New Caledonia. 3 records from A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura: Diogenidae) from southern India. 1434 records from Nannofossil abundance of Hole 94-607. 122 records from Faunal assemblage of sediment core GS7603-8. 2081 records from Thrips (Thysanoptera) in Norway. 1 records from A new species of Homo from the Late Pleistocene of the Philippines. 69 records from Entdeckertour am Muldestausee 1/05. 1 records from Deux nouvelles espèces d’ Aloe L. (Xanthorrhoeaceae, Asphodelaceae), section Lomatophyllum Rowley, de Madagascar. 613 records from Implementación de la bioindicación en el Río Cauca - 2016. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 104 records from BID-Malawi-Arctiidae-Biodiversity-Data. 1879 records from Chronicle of Nature - Phenology of Plants of State Environmental Institution National Park Braslav lakes. 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulidées d'Europe. 21 records from Riedkanal Bötzingen. 54 records from Aves marinas del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 2 records from A new record of the family Isonychiidae (Insecta: Ephemeroptera) from the Western Ghats, India with a description of new species. 20 records from Planktic foraminifera abundance of Hole 19-185. 50 records from (Table T10) Calcareous nannofossil stratigraphy of ODP Hole 198-1212A. 445 records from Enrichment metagenome. 1030501 records from Dragonfly records from the British Dragonfly Society's Dragonfly Recording Network for the period up to 2014. 19021 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) planctónicas más frecuentes en el Golfo de California. 1131 records from eDNA_Subseafloor. 2 records from A new species of Hypsohapsis (Heteroptera: Schizopteridae: Hypselosomatinae) from the Brazilian Amazon. 1824 records from TransForest - vegetation, lichen and fungi data 2016. 31771 records from INVESTIGATING THE MICROBIAL EUKARYOTIC COMMUNITIES IN THE SURFACE WATERS OF THE ARAFURA SEA AND CORAL SEA. 4 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 126 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 146 records from Monitoreo de la vegetación presente en la Cienaga de Beté, Municipio del Medio Atrato-Chocó, 2018. 201 records from Biodiversity of springs and rock seepages 2003. 127 records from Microzooplankton abundance measured on water bottle samples at station PS65/466-2. 10777 records from CEFS_16S_ITS. 36323 records from Biowide Species data. 1194 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 14 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 8 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 1 records from A new riparian Mantidactylus (Brygoomantis) frog from the Tsaratanana and Manongarivo Massifs in northern Madagascar. 521 records from Schanzenanlage Bergham. 140 records from Planktic foraminifera abundance of Hole 37-332. 74 records from Reptiles de la expedición al Río Apaporis - Proyecto Colombia BIO. 24 records from The West Palaearctic Pseudodineura and Endophytus species (Hymenoptera, Tenthredinidae). 1862 records from (Table 2) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Hole 120-748C. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-025. 170 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 98 records from Total foraminifera counts of multinet POS231/3_MSN1332. 75 records from The interstitial subsoil fauna of the lower beach level at Sarso Beach, Red Sea (Table 4). 234 records from Données du Geckos vert des Hauts (Phesulma borbonica) du Parc national de La Réunion. 1 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 906 records from Phytoplankton abundance and species composition in the Tyrrhenian Sea in November 1981. 123 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 3251 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 1 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 8 records from Four new species of Diptilomiopinae from China (Acari: Eriophyoidea: Diptilomiopidae). 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 603 records from Nannofossil abundance of Hole 37-334. 59 records from Schulgelände SGD/Viersen. 69 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 1305 records from Flora genérica de las gramíneas del estado de Tlaxcala. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 247 records from Nannofossil abundance of Hole 84-570. 53 records from Leopard and Weddell seal program 1999/2002. 4309 records from Données naturalistes de Ségolène FAUSTEN. 54 records from Distribución, abundancia y efectos nocivos de tres especies de plantas invasoras. 2 records from Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae). 5464 records from Natural History Museum Maastricht (NL) - Herbarium. 172 records from Foraminifera abundance of sediment core MD81-LC07. 9384 records from MZL Invertebrate Collections. 402 records from Range table from benthic foraminifers in ODP Hole 181-1119C. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 13940 records from Collection of Coleoptera. 74 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 5407 records from Invertebrates of the river Tana Basin in Kenya available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section. 1 records from Karpfenteich, Klasse 6d. 6 records from Range table from planktonic foraminifers in ODP Hole 145-883C. 11 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 170 records from Total foraminifera counts of multinet SO117_MSN1244. 8955 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 15 records from Monitoreo de Murciélagos en la Etapa de Ejecución de las Obras de Ampliación del EPF Floreña, Yopal, Casanare. 3 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 5619 records from uncultured prokaryote Targeted loci environmental. 3435 records from Benthos Chirnov Basin 1986 and 2002. 6 records from (Table 5) Paleotemperature estimates for DSDP Hole 81-552A. 723359 records from Queensland Museum provider for OZCAM. 71 records from Range table from planktonic foraminifers in ODP Hole 182-1133C. 6 records from A taxonomic reappraisal of the Smooth Slug Snake Asthenodipsas laevis (Boie, 1827) (Squamata: Pareidae) in Borneo with the description of two new species. 69 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1379. 192 records from (Table 3) Absolute concentrations and raw counts of seven genera of dinoflagellate in ODP Site 170-1039. 51 records from Coccoliths in sediment core GIK23065-3. 708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 1 records from Molche in Ruschwedel. 133 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 6 records from Two new records and one new species of the genus Apelaunothrips from China (Thysanoptera: Phlaeothripidae). 96 records from Plasm bearing foraminifera counts of multinet M21/1_MSN620. 448 records from (Table 4) Distribution of the large, many-chambered Globigerinelloides species in the Cismon core. 26 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 107 records from Range table from benthic foraminifers in ODP Hole 146-889B. 1 records from A review of New World Malaxa (Hemiptera: Fulgoroidea: Delphacidae). 268 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 190 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 13 records from Microzooplankton abundance and biomass at station NBP97-08-23-6. 150 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 1386 records from Aves de fragmentos de Bosque seco en la región del Caribe Colombiano. 4 records from Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae). 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-093. 2189 records from Jardín Botánico Atlántico, Gijón: JBAG. 26 records from Microzooplankton abundance and biomass at station TT045_26-3. 1419 records from Diversity of algae in wetlands. 1 records from Description of a new species of the Ponerine ant genus, Emeyopone (Hymenoptera: Formicidae) from Karnataka, India.. 751 records from Range table from planktonic foraminifers in ODP Hole 157-954A. 559 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 1137 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 72 records from Données sur les Opisthobranches et Planaires de Mayotte. 1 records from A new species of Rock Gecko of the genus Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from Belitung Island, Indonesia. 562 records from Range table from benthic foraminifers in ODP Hole 189-1169A. 38 records from (Table 1c) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the finishing of the Late Neopleistocene activity phase of the Keli Volcanic Highland. 128 records from Planktic foraminifera abundance of Hole 94-611. 168 records from (Table 1) Distribution of planktonic foraminifera species in Core ML2_66. 10 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI. 3 records from Abundance of zooplankton in the Aral Sea. 105 records from Fish Fauna of Berlin. 7 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 5 records from Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand. 1432 records from Phytoplankton abundance in surface water during cruise CD61. 29 records from Total foraminifera counts of trap L3_92_45. 2004 records from Inventaire des Coléoptères Longicornes des Antilles françaises. 6611 records from Nijmegen Natural History Museum (NL) - Herbarium. 3 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 2573320 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 125055 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 105 records from Total foraminifera counts of trap L2_92_A42. 8 records from Microzooplankton abundance and biomass at station TT054_7-18. 1170 records from Département_du_Var_2017_12_18. 191 records from sediment microorganism Metagenome. 10 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 127 records from Wildlife Observations Bardon Hill 31.5.09. 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Ceará State) and Sete Cidades (Piauí State) National Parks, Northeastern Brazil. 69 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 3 records from Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India. 251 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 5 records from Planktic foraminifera counts of multinet M21/4_MSN724. 1613 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 3455 records from permafrost metagenome Targeted loci environmental. 61726 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 139 records from A new western Canadian record of Epeoloides pilosulus (Cresson). 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 3139 records from CTD water column metabarcoding. 4837 records from Free-living marine Nematodes from San Antonio and Cormoranes sandy beaches (Rio Negro, Argentina), 2006.. 1101 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 2058 records from Table A3. Benthic foraminifera assemblage of sediment core GeoB1710-3. 1880 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv). 28 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 6 records from New species of grasshopper genus Aptoceras Bruner, 1908 (Orthoptera, Acrididae, Ommatolampidinae, Ommtolampidiini) from Iguaçu National Park (Southern Brazil), including a taxonomic key and distribution data. 68 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 3428 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 16 records from A new western Canadian record of Epeoloides pilosulus (Cresson), with discussion of ecological associations, distribution and conservation status in Canada. 343 records from Distribution of planktic foraminifera (250-500 µm) of sediment core GIK23059-3. 313 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_93MC. 725075 records from Finnish Floristic Database (Literature Sources). 7 records from Analyses of the recent components in the sand fraction of sediment core PS1278-1. 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 541 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 2425 records from (Table 14) Calcareous nannofossil occurrences in ODP Hole 130-806B. 72176 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 1773 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 1 records from Microplankton counts and carbon biomass at station TT011_4-CTD46. 633 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 12086517 records from iNaturalist Research-grade Observations. 143 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 65 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 277 records from Aunar esfuerzos y recursos técnicos, económicos y humanos con el fin de adelantar acciones de investigación para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad La Cascada (Valle del Cauca). 175 records from Nannofossil abundance of Hole 41-366A. 3 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 100 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 1820 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 2 records from Description of Penia mantillerii sp. nov. (Coleoptera: Elateridae: Dimini), with a key to Penia species from Vietnam and nearby areas. 2 records from A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 507 records from Planktic foraminifera abundance of Hole 84-567A. 136 records from Nannofossil abundance of Hole 39-359. 1857 records from Range table from planktonic foraminifers in ODP Hole 159-960C. 31 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 17 records from Comunidad de Herpetos presentes en el río Tutunendo, Municipio de Quibdó-Chocó. 4159 records from DBG Mirabilis rotundifolia Demographic Monitoring. 6 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 3 records from Range table from planktonic foraminifers in ODP Hole 178-1102C. 128 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C. 152 records from Nannofossil abundance of Hole 49-412. 7 records from Coeliccia rolandorum sp. nov. from eastern Cambodia and southern Vietnam, the eastern relative of C. kazukoae Asahina, 1984 (Odonata: Platycnemididae). 2 records from Molecular phylogeny of Hiptage (Malpighiaceae) reveals a new species from Southwest China. 26 records from Abundance of benthos infauna at station PS1240-1. 611 records from Données du Râle gris sur le territoire de la Guadeloupe. 8 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 33 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 994 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 12 records from Microzooplankton abundance and biomass at station NBP97-03-12-2. 18 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5120-2. 1135 records from MarineGEO visual diver surveys of fish communities around Carrie Bow Cay, Belize, 2015. 168 records from (Table 2) Distribution of selected planktonic foraminifer species at ODP Site 124-770. 701 records from Données naturalistes d'Arnaud LE NEVÉ. 2141 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 23675 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 12 records from Analyses of the recent components of sediment core PS1219-1. 717 records from Redland City Council Citizen Science Portal. 1 records from New Zealand forest-dwelling skinks of the Oligosoma oliveri (McCann) species-complex (Reptilia: Scincidae): reinstatement of O. pachysomaticum (Robb) and an assessment of historical distribution ranges. 9 records from New species, new records, and new collection data of Rhyacophila from China (Trichoptera: Rhyacophilidae). 239 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 339 records from HBRG Invasive Non-native Plants Dataset. 253 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 1070 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 3251 records from Inventario florístico de la Sierra de Huautla, Morelos. 851 records from Pollen profile V and Ausfluss at Krumbach, Germany. 547 records from Inventario de sanguijuelas (Annelida: Clitellata Hirudinea) de México, con énfasis en las especies del centro de México. 1 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 229 records from Queen Charlotte Sound / Tōtaranui and Tory Channel / Kura Te Au (HS51) Hydrographic Survey Marine Mammal Observations. 186362 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 355 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (75° N section). 5 records from Two new species of Guyruita Guadanucci et al., 2007 (Araneae, Theraphosidae) from Brazil. 3 records from New species of Graphocaecilius Enderlein (Psocodea: ‘ Psocoptera’: Lachesillidae) from Colombia. 1 records from A new species of Polyipnus (Stomiiformes: Sternoptychidae) from the Western South Pacific. 93 records from Wildlife Sightings in the City of Logan. 13545 records from Temporal dynamics of bacterioplankton community in response to excessive nitrate loading in the oligotrophic coastal water. 16253 records from Birds Specimens. 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 125 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 74-525A. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 86 records from Fliegenhaupt Marksuhl. 56 records from Planktic foraminifera abundance of Hole 23-227. 66 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 16756 records from DMNS Mammal Collection (Arctos). 2199 records from Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009. 43 records from (Table 9) Biological parameters of stratigraphic horizons in Core AMK7-734 according to foraminifera. 110 records from Occurrence of mammalia relicts at site Rejtek 1. 1 records from A new species of the genus Pachytriton (Caudata: Salamandridae) from Hunan and Guangxi, southeastern China. 226 records from (Table 2) Stable oxygen and carbon data, and relative abundances of selected planktonic foraminiferal species in the surface sediment samples retrieved during the SO-189 cruise off W Sumatra. 2281 records from Relative abunances of benthic foraminifera in Late Oligocene to Miocene sediments of ODP Hole 121-757B from the southeastern Indian Ocean (Appendix Table 1). 1 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 881 records from Relative abundance of adult opstracoda shells of surface sediment samples from the Persian Gulf (Table 1b). 81 records from Taxonomic review of the ladybird genus Sticholotis from China (Coleoptera: Coccinellidae). 785 records from Colección de Mamíferos Marinos del Centro Nacional Patagónico. 1028 records from IBF Monitoring of Fungi. 4 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 2242 records from (Table 3) Distribution of planktonic foraminifera in the early Cretaceous and early Eocene to late Oligocene sections of ODP Hole 149-897C. 27 records from Benthic foraminifera and algae abundance of Hole 81-553. 1 records from A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae). 108 records from Total foraminifera counts of multinet M21/2_MSN629. 154 records from Planktic foraminifera assemblage in sediment core GIK23065-2. 1 records from Schulman's Neotropical Adelobotrys database. 12094 records from Amino acid addition experiment Metagenome. 194 records from Colección Herpetológica de la Patagonia. 55 records from Vegetationsmatrix schorfheide alb 2008 durchgang2. 152 records from Total foraminifera counts of multinet POS247/2_MSN1372. 1 records from Dinoflagellate abundance of Hole 85-572C. 39345 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 1308 records from Comparative metagenome analysis of normal and arsenic contaminated soils from ballia district, Uttar Pradesh, India. 33 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 9054 records from Highland bird data 2002 - 2003 - non-breeding records. 9349 records from Harriet Irving Botanical Gardens (HIBG). 46092 records from Weed and native flora data for the Swan Coastal Plain. 99 records from Total foraminifera counts from M35/1_MSN1061. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 9002 records from Uncultured Environmental Isolate Targeted loci environmental. 4158 records from RNF - Données du Parc Naturel Régional du Vercors. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 1941 records from (Table 19) Ranges of benthic foraminifers from the late Neogene through the Pleistocene in ODP Hole 115-707A. 3078 records from Insectes Hyménoptères Scollidés de France. 1 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 4717 records from Weddell Sea macrozoobenthos EASIZ I. 1345 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 916 records from IOW Natural History & Archaeological Society Marine Records. 2851 records from sea water Picoeukaryotic Community Raw sequence reads Raw sequence reads. 13 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 6189 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 71 records from Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_10-CTD124. 2528 records from Communauté_de_communes_Asse_Bléone_Verdon_2017_12_18. 10865 records from Seawater metagenome Targeted loci environmental. 14 records from Occurrence of mammalia relicts at site Climauti II. 354 records from Phytoplankton abundance measured on water bottle samples at station PS65/545-1. 142 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 135 records from Waldi-Weiher. 4751 records from Composition of planktonic foraminifera species from 310 sediments samples during the last glacial maximum. 210 records from (Table 1) Distribution of foraminifera in the Miocene section of ODP Hole 133-815A. 470 records from Gewann Krampf (Heilbronn). 4 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 17 records from Benthic macrofauna abundance of sediment core 13201-002. 64 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 320 records from (Table S1) Nannofossil abundances at DSDP Hole 86-577. 493 records from Fauna and population of oribatid mites (Acari, Oribatida) in the vicinity of Kosogorsky metal works (Tula Region, Russia). 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 607 records from Inventory of Bassila forest (North-Benin). 1013 records from Circumpolar Seabird Monitoring Plan. 421 records from Pollen profile from Muscotah Marsh B. 29 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 48 records from Catch related distribution of Appendicularia at station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 8). 1 records from Rhopalomenia glandulosa spec. nov., and the restoration of Entonomenia Leloup (Mollusca: Solenogastres). 6441 records from Microbial ecology of bacteiral community in sediment from adjacent waters of Rushan Bay. 718 records from Planktic foraminifera assemblage of sediment core ELT49.023-PC. 120 records from (Table 10) Occurrence of benthic foraminifera in ODP Hole 112-688E, Part II. 80 records from (Table 2) Relative abundances of shallow-water foraminifera in ODP Hole 133-821A. 3 records from The larva of Lestes alfonsoi Gonzalez & Novelo (Zygoptera: Lestidae). 38 records from Phytoplankton counted on two fractions of surface sediment samples from stations B-5 to B-47. 30 records from Planktic foraminifera abundance of Hole 14-144. 2 records from Revision of Terellia amberboae group of species (Diptera: Tephritidae). 3102 records from seawater metagenome Metagenome. 819 records from Inventaire National du Patrimoine Naturel : CBN de Midi-Pyrénées. 364 records from (Table 10) Distribution of coccoliths in Core AMK7-734 from the Tajura Rift. 4372 records from Heliconiine Butterfly Collection Records from University of Cambridge. 800 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 2436 records from Diet results from Adelie penguins at Bechervaise Island and Whitney Point, 2012/13. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 5 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 6 records from (Table 1) Nesting characteristics of greater snow geese (Chen caerulescens atlanticus) on Bylot Island between 1995-2005. 12 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 157 records from Planktic foraminifera counts at CTD station PS55/078-1. 355 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 439 records from Collection Echinodermata - ZMB. 244 records from WildesMoor bei Schwabstedt. 435 records from Inventario herpetofaunístico del noroeste de Hidalgo. 391 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 677 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 3 records from Three new species of jumping spiders of the genus Hypaeus Simon, 1900 from Colombia (Salticidae: Salticinae: Amycini). 2 records from Description of lithologic section units of IODP Hole 325-M0052A. 9366 records from ZooplanktonBeaufortSeaNOGAP2. 7 records from Update of the genus Leptochiton (Mollusca: Polyplacophora) in Chilean deep waters: three new reports and description of two new species. 7920 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 331 records from (Table IIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of the Ben Gurion Section, Israel. 20 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_276-1. 61 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 18 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 35 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/091-4. 6 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 4 records from A Catalogue and Historical Study of the Odonata of Ecuador. 193 records from Planktic foraminifera abundance of Hole 94-610. 4617 records from Códigos de barras de la vida en peces y zooplancton de México. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 39580 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 69 records from (Table 5) Abundance of selected helicoliths at DSDP Site 82-563 in the North Atlantic. 4 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR50. 4 records from Two new species of Dentilabus Heinrich (Hymenoptera: Ichneumonidae: Ichneumoninae) from Japan and Korea, with redefinition of the genus. 5 records from Loricifera - SMF. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 13 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 243 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 479121 records from KTP Ring Data. 1 records from Two new species of Darnini (Hemiptera: Membracidae) from Colombia and Peru. 49 records from Données naturalistes (Rhopalocères et Zygènes) de Bob WHITMARSH (indépendant). 4 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 1 records from Synthèse de la Répartition des populations de cerf élaphe en 2000 (réseau Ongulés sauvages ONCFS-FNC-FDC). 16464 records from Arbeitsgemeinschaft Heuschrecken Österreichs. 11 records from Données d'observation opportunistes collectées durant la campagne de prélèvements sédimentaires SHELL/CREOCEAN en Guyane française en 2013. Shell Exploration and Production France. 1422 records from Australian Institute of Marine Science (AIMS) - Lizard Island Reef Biodiversity Expedition, Queensland, Australia (2008 - 2009). 483 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 41 records from Morphologische Daten von Natrix. 12699 records from Soil metagenome from healthy and unhealthy agricultural soil. 12458 records from Brown University Herbarium. 103 records from Collection botanique Lamy de la Chapelle E. (BOUM). 1703 records from (Table 3) Ranges of benthic foraminifers from the late Eocene through the Oligocene in ODP Hole 115-707A. 875 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 95 records from BIRDRACE accipiter hardcore birding. 324 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 89 records from Occurrence of mammalia relicts at site Spitzbubenhöhle. 23 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 1 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 1 records from A new genus and species of entocytherid ostracod (Ostracoda: Entocytheridae) from the John Day River Basin of Oregon, U. S. A., with a key to genera of the subfamily Entocytherinae. 58 records from LISU Herbario Angola. 712 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 309 records from CNAC/Coleccion Nacional de Acaros. 2 records from Intraspecific variation in adult Uvitellina iraquensis Dronen, Ali & Al-Amura, 2013 (Cyclocoelidae: Haematotrephinae) from two collection sites of white-tailed lapwing, Vanellus leucurus (Lichtenstein) (Charadriiformes: Charadriidae), in Iraq. 2173 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 229 records from Distribución y estructura poblacional de la tortuga de Berlandier, (Gopherus [=Xerobates] berlandieri) en México. 332 records from Nannofossil abundance of Hole 4-31. 628 records from hauterivian_echinoids_of_the_paris_basin. 48 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1197. 14 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_3-CTD4. 7582 records from Tropical epiphyte diversity under human impact ? Comparing primary forests, secondary forests, and forest fragments in Ecuador - Otonga. 24 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 179 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 2 records from A new ant species of the Leptogenys sulcinodagroup (Hymenoptera: Formicidae) from Saudi Arabia. 1477 records from Inventaire des espèces végétales productives dans les Systèmes Agro-forestiers aux alentours de la Forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 201 records from BioAcoustica: Wildlife Sounds Database. 140 records from (Table 2) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-753A. 3 records from Otacilia fansipan spec. nov., the second congener recorded from Vietnam (Arachnida: Araneae: Phrurolithidae). 4 records from Determinación de la clase Reptilia presente en el corregimiento de Juanchaco, Valle del Cauca, Colombia para el mes de Septiembre de 2017. 255 records from Tejidos colectados en el páramo de Pisba, Boyacá - Proyecto Boyacá BIO. 10 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 30-63 µm fraction. 79 records from Birdrace-Bielefinken-Bielefeld. 107 records from Müritz-Nationalpark. 125 records from Range table from ostracoda in ODP Hole 143-866B. 8646 records from Kenai National Wildlife Refuge, Alaska (KNWR) Insect specimens (Arctos). 4054 records from Fish specimens of Toyama Science Museum. 65 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-2. 913 records from Phytoplankton abundance in surface water in October 1997, Pisco, Peru. 6004 records from Colección Limnológica Universidad de Antioquia. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 378 records from Rock ptarmigan (Lagopus muta) radio telemetry in Lierne, Norway. 272 records from Wald am Schloss Wittgenstein Bad Laasphe. 503 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Peces (MG-ZV-P). 140748 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 4 records from Pheronema on the mid-Atlantic Ridge, data from NRCan. 239 records from Shoreline fish distribution in Italian lakes assessed by electrofishing. 3529 records from A dataset from bottom trawl survey around Taiwan. 35 records from Phytoplankton abundance in surface water in 2003, Ancon, Peru. 3 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 41 records from Phytoplankton abundance at station Sechin_2003-10-03_2, Casma, Peru. 816 records from Inventarios de la biodiversidad en el piedemonte subandino de Yopal. 2 records from Two new species of stargazers of the genus Uranoscopus (Teleostei: Uranoscopidae) from the western Pacific Ocean. 105 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 743 records from Données naturalistes de François BRETON. 8 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 20 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2004. 1 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 210 records from Large protozoa abundance measured on concentrated water b
Keywords: GBIF; biodiversity; species occurrences